2023
DOI: 10.3390/life13112206
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori (H. pylori) Infection-Associated Dyslipidemia in the Asir Region of Saudi Arabia

Mohammad Asrar Izhari,
Omar A. Al Mutawa,
Ali Mahzari
et al.

Abstract: Objectives: H. pylori-associated dyslipidemia has been reported to be a major risk factor for atherosclerosis and coronary heart diseases. We aimed to investigate the association of the H. pylori infection with dyslipidemia. Methods: A retrospective case–control study was undertaken to evaluate H. pylori-associated dyslipidemia, where H. pylori-positive individuals were treated as the case group (n = 260) while H. pylori-negative individuals were considered as the control group (n = 250). The mean ± SD of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Our focus on the altered lipid profile stems from its crucial role in cardiovascular disease. The association between H. pylori and cardiovascular disease has been a subject of debate in several studies (36,37). Our study concluded that patients with H. pylori exhibit an altered lipid profile compared to patients without H. pylori.…”
Section: Histopathology Aspects Of the Gastric Mucosa Using He And Gi...mentioning
confidence: 62%
“…Our focus on the altered lipid profile stems from its crucial role in cardiovascular disease. The association between H. pylori and cardiovascular disease has been a subject of debate in several studies (36,37). Our study concluded that patients with H. pylori exhibit an altered lipid profile compared to patients without H. pylori.…”
Section: Histopathology Aspects Of the Gastric Mucosa Using He And Gi...mentioning
confidence: 62%